FACTORS AFFECTING QUALITY OF BASIC DESIGN OF THE TRANSPORT INVESTMENT CONSTRUCTION PROJECTS IN HOCHIMINH CITY - Sang, Nguyen Van; Phuong, Nguyen Hoang (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents the research results identifying the factors affecting the quality of basic design of the transport investment construction projects in Hochiminh City. The survey was conducted in Hochiminh City, focusing on the subjects working at consultingy units, investors and specialized state agencies. 190 surveys were issued, among which there are 140 valid responses, 6 main groups of factors affecting the quality of basic design were indetified, including: Project consulting and setting up contractor, Investor, Project budget, standards – legislation, the compatibility between basic design, technical design and science and technology. The exploratory factor analysis (EFA) was used to assess the influence levels of the factors. The management implications and basis of the proposed solution were also presented.